2008
DOI: 10.1007/s00299-008-0523-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of selection strategies alternative to nptII in genetic transformation of citrus

Abstract: The neomycin phosphotransferase (nptII) selection system has proved successful in citrus transformation; however, it may be recommendable to replace it given the pressure exerted against antibiotic-resistance selectable marker genes in transgenic plants. The present work investigates three different selection alternatives, comparing them to nptII selection in two citrus genotypes, Carrizo citrange and Pineapple sweet orange. The first method used the beta-glucuronidase (uidA) reporter marker gene for selection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
45
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(48 citation statements)
references
References 33 publications
2
45
1
Order By: Relevance
“…The pmi/Man system has been successfully used in several plant systems such as sugar beet (Joersbo et al 1998), cassava (Zhang and Puonti-Kaerlas 2000), maize (Negrotto et al 2000;Wright et al 2001), Arabidopsis (Todd and Tague 2001), wheat , tobacco and potato (Kunze et al 2001), pepper (Kim et al 2002), sweet orange (Boscariol et al 2003), pearl millet (O'Kennedy et al 2004), tomato (Sigareva et al 2004, papaya (Zhu et al 2005), bentgrass (Fu et al 2005), apple (Degenhardt et al 2006), onion (Aswath et al 2006), almond (Ramesh et al 2006), cucumber (He et al 2006), cabbage (Min et al 2007), sugarcane (Jain et al 2007), flax (Lamblin et al 2007), citrus (Ballester et al 2008), sorghum (Gurel et al 2009) and chickpea (Patil et al 2009). However, the pmi/Man system has not been tested previously in Oncidium orchid.…”
Section: Introductionmentioning
confidence: 99%
“…The pmi/Man system has been successfully used in several plant systems such as sugar beet (Joersbo et al 1998), cassava (Zhang and Puonti-Kaerlas 2000), maize (Negrotto et al 2000;Wright et al 2001), Arabidopsis (Todd and Tague 2001), wheat , tobacco and potato (Kunze et al 2001), pepper (Kim et al 2002), sweet orange (Boscariol et al 2003), pearl millet (O'Kennedy et al 2004), tomato (Sigareva et al 2004, papaya (Zhu et al 2005), bentgrass (Fu et al 2005), apple (Degenhardt et al 2006), onion (Aswath et al 2006), almond (Ramesh et al 2006), cucumber (He et al 2006), cabbage (Min et al 2007), sugarcane (Jain et al 2007), flax (Lamblin et al 2007), citrus (Ballester et al 2008), sorghum (Gurel et al 2009) and chickpea (Patil et al 2009). However, the pmi/Man system has not been tested previously in Oncidium orchid.…”
Section: Introductionmentioning
confidence: 99%
“…Complete excision of marker genes ranged from 5 to 12 months, however, only 41% of the regenerated transgenic shoots R-mediated recombination occurs correctly. In Citrus sp., it was also reported that anomalous excision of marker genes promoting failures in the expression of the reporter genes (Ballester et al, 2007(Ballester et al, , 2008.…”
Section: Alternative Transformation Systems: Transgenics Without Markmentioning
confidence: 99%
“…Sensitivity to the toxic effect of mannose-6-phosphate is different between species, and can be avoided by combining with other sugars such as sucrose, maltose and fructose (Joersbo et al, 1999). Diverse fruit trees were selected with this system, alone or in combination with sucrose, i.e., 12 g/L mannose and 5 g/L sucrose in orange (Ballester et al, 2008); 30 g/L mannose without any sugar more in papaya (Zhu et al, 2005); 2,5 g/L www.intechopen.com mannose and 5 g/L sucrose in almond (Ramesh et al, 2006) or 1-10 g/L mannose and 5-30 g/L in apple (Degenhardt et al, 2006). In Citrus sinensis, the best results were obtained when 13 g/L mannose as unique source of carbon was added into the selection media.…”
Section: Selection Systems a Critical Stepmentioning
confidence: 99%
“…No Agrobacterium was involved and there was no selective agent applied. Ballester et al (2008) compared the most common citrus transformation and selection system, using kanamycin selection and scorable GUS staining to three methods that did not utilize antibiotic selection, in 'Carrizo' citrange and 'Pineapple' sweet orange. The alternative methods included scoring for GUS staining without applying selection, transforming explants with a multi-autotransformation (MAT) vector, combining an inducible recombinase-specific recombination system (R/RS) with transgenic-shoot selection through expression of isopentenyl transferase (ipt) and indoleacetamide hydrolase/tryptophan monooxygenase (iaaM/H) marker genes, and selection with the PMI/mannose conditional positive selection system .…”
Section: Conclusion: the Future Of Citrus Transformationmentioning
confidence: 99%